The Current Status and Future Potential of Theranostics to Diagnose and Treat Childhood Cancer - Poot, Alex J.; Lam, Marnix G. E. H.; van Noesel, Max M. (Frontiers in Oncology, 2020)
In Theranostics (i.e. therapy and diagnostics) radiopharmaceuticals are used for both therapeutic and diagnostic purposes by targeting one specific tumor receptor. Biologically relevant compounds, e.g. receptor ligands or drugs, are labeled with radionuclides to form radiopharmaceuticals. The possible applications are multifold: visualisation of biological processes or tumor biology in vivo, diagnosis and tumor staging, therapy planning and treatment of specific tumors. Theranostics research is multi-disciplinary and allows for the rapid translation of potential tumor targets from preclinical research to “first-in-man” clinical studies. In the last decade, the use of theranostics has seen an unprecedented value for adult cancer patients. Several radiopharmaceuticals are routinely used in clinical practice (e.g. [68Ga/177Lu]DOTATATE) and dozens are under (pre)clinical development. In contrast to these successes in adult oncology, theranostics have scarcely been developed to diagnose and treat pediatric cancers. To date, [123/131I]meta-iodobenzylguanidine ([123/131I]mIBG) is the only available and approved theranostic in pediatric oncology. mIBG targets the norepinephrine transporter, expressed by neuroblastoma tumors. For most pediatric tumors, including neuroblastoma, there is a clear need for novel and improved radiopharmaceuticals for imaging and therapy. The strategy of theranostics for pediatric oncology can be divided in: (1) the improvement of existing theranostics; (2) the translation of theranostics developed in adult oncology for pediatric purposes; and (3) the development of novel theranostics for pediatric tumor-specific targets. Here we describe the recent advances in theranostics development in pediatric oncology and shed a light on how this methodology can affect diagnosis and provide additional treatment options for these patients.